Relationship between enriched environment and neurodegeneration: a review from mechanism to therapy - Yuan-qiao Xu; Yanjiao Chen; Jia-xin Xing; Jun Yao (Clinical Epigenetics)
Abstract Enriched environment (EE), as a non-pharmacological intervention, has garnered considerable attention for its potential to ameliorate neurodegenerative diseases (NDs). This review delineated the impact of EE on the biological functions associated with NDs, emphasizing its role in enhancing neural plasticity, reducing inflammation, and bolstering cognitive performance. We discussed the molecular underpinnings of the effects of EE, including modulation of key signaling pathways such as extracellular regulated kinase 1/2 (ERK1/2), mitogen-activated protein kinases (MAPK), and AMPK/SIRT1, which were implicated in neuroprotection and synaptic plasticity. Additionally, we scrutinized the influence of EE on epigenetic modifications and autophagy, processes pivotal to ND pathogenesis. Animal models, encompassing both rodents and larger animals, offer insights into the disease-modifying effects of EE, underscoring its potential as a complementary approach to pharmacological interventions. In summary, EE emerges as a promising strategy to augment cognitive function and decelerate the progression of NDs.